1992
DOI: 10.1021/bi00131a015
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor and its extracellular soluble domain: the relationship between intermolecular association with factor VIIa and enzymic activity of the complex

Abstract: We find that the isolated, extracellular domain of tissue factor (TF1-218; sTF) exhibits only 4% of the activity of wild-type transmembrane TF (TF1-263) in an assay that measures the conversion of factor X to Xa by the TF:VIIa complex. Further, the activity of sTF is manifest only when vesicles consisting of phosphatidylserine and phosphatidylcholine (30/70 w/w) are present. To determine whether the decreased activity results from weakened affinity of sTF for VIIa, we studied their interaction using equilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
81
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 40 publications
12
81
2
Order By: Relevance
“…Owing to the threshold nature of the TF-triggered thrombin generation, this < 5-fold difference in the catalytic efficiency leads to dramatic changes in thrombin generation in complex systems representing the blood coagulation process (Figure 4 ). These data indicate that, in contrast to previously published statements suggesting that post-translational modifications have no effect on TF activity (Paborsky and Harris , 1990 ;Waxman et al , 1992 ), TF glycosylation has a pronounced effect on factor X proteolysis by the factor VIIa-TF complex and, as a consequence, on thrombin generation.…”
Section: Glycosylationcontrasting
confidence: 91%
See 1 more Smart Citation
“…Owing to the threshold nature of the TF-triggered thrombin generation, this < 5-fold difference in the catalytic efficiency leads to dramatic changes in thrombin generation in complex systems representing the blood coagulation process (Figure 4 ). These data indicate that, in contrast to previously published statements suggesting that post-translational modifications have no effect on TF activity (Paborsky and Harris , 1990 ;Waxman et al , 1992 ), TF glycosylation has a pronounced effect on factor X proteolysis by the factor VIIa-TF complex and, as a consequence, on thrombin generation.…”
Section: Glycosylationcontrasting
confidence: 91%
“…A possible lack of interest to TF glycosylation could be explained by the influence of several studies published approximately two decades ago. In those studies, the carbohydrates were reported to be insignificant for the activity of TF (Waxman et al , 1992 ;Stone et al , 1995 ;Rickles et al , 1996 ) owing to a similar activity of the non-glycosylated recombinant protein from Escherichia coli and the glycosylated one from kidney 293 cells (Paborsky and Harris , 1990 ). In contrast to those publications, data from other laboratories (Pitlick , 1975 ;Shands , 1985 ;Bona et al , 1987 ) suggested that carbohydrates could play a role in the activity of TF.…”
Section: Glycosylationmentioning
confidence: 98%
“…Our results (Table 1) on intact FVII, intreaction with detergent solubilized TF (KTF = 0.6 + 0.1 nM) and with TFl_21 s (Kaw = 6.0 -+ 0.4 nM) agrees reasonably well with previous values [22,27]. Much lower values (KvF = 7--27 pM) have, however, been obtained in recent studies with TF in (PC/PS) phospholipid vesicles [27,30] thus indicating that membrane constituents may contribute to stabilization of the complex.…”
Section: The 'Hydrophobic Stack'supporting
confidence: 87%
“…It has been shown that binding of TF to factor VII~ in the presence of Ca 2+ induces a pronounced enhancement of the activity with peptidyl substrates [25], and this [5,16,22,[26][27][28] as well as other methods [29,30] have been used for the assessment of the dissociation constant, KTF. Our results (Table 1) on intact FVII, intreaction with detergent solubilized TF (KTF = 0.6 + 0.1 nM) and with TFl_21 s (Kaw = 6.0 -+ 0.4 nM) agrees reasonably well with previous values [22,27].…”
Section: The 'Hydrophobic Stack'mentioning
confidence: 99%
“…Recombinant soluble human tissue factor (sTF, residues 1 to 217) was expressed in yeast and purified according to a published method. 33 The sTF concentration was determined by using a 1% extinction coefficient at 280 nm of 14.9 34 and a molecular weight of 37 000. 33 The clot-based assay for FVIIa was originally developed by Morrissey et al 31 We modified it as follows.…”
Section: Assay Of Fviiamentioning
confidence: 99%